Myocardial dysfunction in patients with aortic stenosis and hypertensive heart disease assessed by MR tissue phase mapping. Issue 1 (21st December 2015) - von Knobelsdorff‐Brenkenhoff, Florian; Hennig, Pierre; Menza, Marius; Dieringer, Matthias A.; Foell, Daniela; Jung, Bernd; Schulz‐Menger, Jeanette
Abstract : Purpose: To identify abnormalities of myocardial velocities in patients with left ventricular pressure overload using magnetic resonance tissue phase mapping (TPM). Material and Methods: Thirty‐three patients (nine with hypertensive heart disease [HYP], 24 with aortic stenosis [AS]) and 41 healthy controls were enrolled. To assess left ventricular motion, a basal, midventricular, and apical slice were acquired using three‐directional velocity‐encoded phase‐contrast MR with a 3T system. Target parameters were peak longitudinal (Vz ) and radial (Vr ) velocity in systole and diastole (Peaksys, Peakdias ). Analysis was done on each myocardial segment. In a subgroup ( n = 7 HYP, n = 12 AS, n = 24 controls), measurement was repeated during handgrip exercise. Results: AS had significantly lower Vz ‐Peaksys in the inferolateral and inferoseptal wall ( P = 0.003–0.029) and Vr ‐Peaksys in the septum and anterior wall ( P = 0.001–0.013) than controls. Vz ‐Peakdias and Vr ‐Peakdias were lower in AS than in controls in almost all segments ( P < 0.001–0.028). HYP showed reduced Vz ‐Peakdias compared to controls in all basal segments as well as in the lateral midventricular wall ( P < 0.001–0.045), and reduced Vr ‐Peakdias compared to controls predominantly in the midventricular and apical segments ( P = 0.004–0.042). AS patients with focal fibrosis had significantly reduced myocardial velocities ( P = 0.001–0.047) in segments without late enhancement. During exercise, Vz ‐Peaksys, Vr ‐Peaksys, and Vz ‐Peakdias remained unchanged in AS and HYP, but decreased in the lateral wall in controls ( P < 0.001–0.043). Conclusion: Even with preserved left ventricle (LV) ejection fraction, peak longitudinal and radial velocities of the LV are reduced in AS and HYP, indicating early functional impairment. J. Magn. Reson. Imaging 2016;44:168–177.